The gift [videorecording (DVD)] - Edgerton, Joel, 1974-; Edgerton, Joel, 1974-; Bateman, Jason; Hall, Rebecca, 1982-; Edgerton, Joel, 1974- (Universal Studios Home Entertainment, 2015)
A young married couple's lives are thrown into a harrowing tailspin when an acquaintance from the husband's past brings mysterious gifts and a horrifying secret to light after more than twenty years.